Roman council of 382 in the context of ecclesiastical andpolitical activities and ecclesiological views of St. Damasus of Rome and St. Ambrose of Milan - Georgy Zakharov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article is devoted to the historical signifi cance and ecclesiology of the council of Rome, 382. It considers this council to be the fi nal point in the history of the Arian crisis in the Latin West. The original plan of the Western emperor Gratianus, supported by the Roman pope Damasus and St. Ambrose of Milan, to hold the council in the general format, was not fully implemented due to the convening by the Eastern emperor Theodosius of the parallel council in Constantinople. In spite of this, the Roman council took a number of important decisions, both ecclesiastico-political and doctrinal. Our study proceeds following the traditional attribution of the third part of the so-called Decretum Gelasianum to the Roman council of 382. The ecclesiology of the council was the result of a compromise: on the one hand, it expresses the desire of St. Damasus to demonstrate the unique character of the Roman primacy and its Divine, rather than synodal origin; on the other hand, the Roman see divides the primacy with the two eastern sedes Petri, i.e. Alexandria and Antioch. The article points to the importance of the theme of the primacy of Peter and the special authority of the Roman see in the ecclesiology of St. Ambrose of Milan. At the same time, we come to the conclusion that for him the Roman primacy was inseparably linked with the idea of the conciliar consent of the Western episcopate and its “superiority” over the Eastern. The expression of this consensus of the Roman see with the episcopate of the West was the council of Rome, 382.